2016
DOI: 10.4306/jknpa.2016.55.4.450
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Anxiety, Self-Esteem, and Depression on Suicidal Ideation in Korean Adolescents

Abstract: ObjectivesZZThe purpose of this study was to investigate the manner by which social anxiety symptoms, self-esteem, and depression influence suicidal ideation in adolescents.MethodsZZThis study involved 1320 middle school students. All participants completed several self-assessment questionnaires. Correlations among variables were assessed, and multiple regression analysis was performed to evaluate the relationships between variables and suicidal ideation. Finally, a structural equation model was used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…De hecho, la predicción de la autoestima en la ideación suicida se manifestó a través de la competencia negativa (apreciación negativa de otras personas hacia sí mismo). En estudios conducidos en diferentes escenarios se ha comprobado que la baja autoestima es un factor asociado a la ideación suicida en adolescentes con depresión (52)(53)(54), y que autoestima y depresión interactúan en la ideación suicida; es decir, al aumentar la depresión disminuye la autoestima, lo que lleva a la ideación suicida (55). Incluso, en un estudio longitudinal se señalan las relaciones entre estas variables, indicando que la autoestima se puede considerar como un predictor de la depresión, pero no viceversa (56).…”
Section: Discussionunclassified
“…De hecho, la predicción de la autoestima en la ideación suicida se manifestó a través de la competencia negativa (apreciación negativa de otras personas hacia sí mismo). En estudios conducidos en diferentes escenarios se ha comprobado que la baja autoestima es un factor asociado a la ideación suicida en adolescentes con depresión (52)(53)(54), y que autoestima y depresión interactúan en la ideación suicida; es decir, al aumentar la depresión disminuye la autoestima, lo que lleva a la ideación suicida (55). Incluso, en un estudio longitudinal se señalan las relaciones entre estas variables, indicando que la autoestima se puede considerar como un predictor de la depresión, pero no viceversa (56).…”
Section: Discussionunclassified
“…청소년의 자살 생각에 영향을 미치는 요인으로는 성 별, 학년 등의 인구사회학적 특성 뿐 아니라 우울, 자기통제 력, 자아존중감 등의 개인체계 변수, 부모의 자녀학대, 가정 폭력, 부모애착 등의 가족체계 변수, 친구 관계, 따돌림 등의 또래체계 변수 및 교사의 지지, 학교 폭력, 학업 스트레스 등 의 학교체계 변수로 다양하다 (Hong SH et al, 2016 (Oh SG, 2006;Min AR et al, 2014;Shin HJ et al, 2014 (Kim SW et al, 2010;Min AR et al, 2014;Sohn SY, 2014;Kim EK, 2018 (Park JY, 2010;Kang HY et al, 2013). 더불어 청소년기 학교적응 및 스트레스와 관련된 갈등, 두려움 등으로 인한 불안은 자존감 저하나 우울과 밀접한 관계를 맺게 되고 이는 다시 자살문제로 연결될 수 있다 (Kim GS et al, 2012;Yao et al, 2014;An YS et al, 2016…”
Section: 국내 중학생의 자살생각은 연구에 따라 차이가 있으나unclassified
“…Some studies have found that low self‐esteem is directly related to depression (Tripkovic et al, 2015; Yoo et al, 2015) and indirectly related to SI (Lin, 2015a). Other studies have revealed the mediating role of self‐esteem in the relationship between negative/stressful events and depression/suicide (An et al, 2016; J. Y. Kim & Lee, 2015; Lin, 2015b; Yusufov et al, 2017). In other words, low self‐esteem has been suggested to be an important predictor of depression, SI, and suicide attempt (Jo & Seong, 2016; J. Y. Kim & Lee, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have found that low self-esteem is directly related to depression (Tripkovic et al, 2015;Yoo et al, 2015) and indirectly related to SI (Lin, 2015a). Other studies have revealed the mediating role of self-esteem in the relationship between negative/stressful events and depression/suicide (An et al, 2016; J. Y. Lin, 2015b;Yusufov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%